Naprężenia momentowe w zagadnieniu-kontaktowym dla pasma nieskończonego - Dusza, A.; Sokołowski, M. (Engineering Transactions, 1968)
An infinite elastic layer or a plate strip is compressed between two semi-infinite rigid blocks. Both the static and the quasi-static problems have been considered, the latter assuming that theblocks move at a constant velocity along the surfaces of the layer. The couple-stresses seem to be responsible for a considerable increase of the stress concentration factor; a similar influence is observed with respect to the critical value of velocity c at which a resonance with the surface waves in a Cosserat-type medium should be expected.